2015
DOI: 10.1039/c5ta05053g
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-lightweight PANiNF/MWCNT-functionalized separators with synergistic suppression of polysulfide migration for Li–S batteries with pure sulfur cathodes

Abstract: A custom separator with an ultra-lightweight polyaniline nanofibers/multiwall carbon nanotubes (PANiNF/MWCNT) coating has been utilized in lithium-sulfur (Li-S) battery for investigating the electrochemical performance of a hybrid conductive-polymer/carbon coating.The cells employing the PANiNF/MWCNT-functionalized separators facilitate high reversible capacities of 709, 641, and 612 mA h g -1 at, respectively, C/5, C/2, and 1C rates after 100 cycles.High charge-storage capacity retention was also found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 25 publications
0
82
1
1
Order By: Relevance
“…The voltage hysteresis (Δ E ) between charge and discharge curves at the point of 50 % of the discharge capacity was considered an important parameter for assessing the energy efficiency of the sulfur cathode. The S/KB@C 3 N 4 /GS cathode shows a Δ E value of approximately 0.18 V, which is slightly smaller than the values reported in previous studies . It was found that Δ E values increased as the rate increased; nevertheless, the speed of the increase was different for the two cathodes.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The voltage hysteresis (Δ E ) between charge and discharge curves at the point of 50 % of the discharge capacity was considered an important parameter for assessing the energy efficiency of the sulfur cathode. The S/KB@C 3 N 4 /GS cathode shows a Δ E value of approximately 0.18 V, which is slightly smaller than the values reported in previous studies . It was found that Δ E values increased as the rate increased; nevertheless, the speed of the increase was different for the two cathodes.…”
Section: Resultscontrasting
confidence: 62%
“…There have been many efforts to apply interlayers of various structures and compositions—including conductive polymers, metal–organic frameworks (MOFs), transition‐metal sulfides,, oxides, and nitrides,, and carbonaceous materials—to improve the electrochemical performance of Li–S batteries. Conductive polymer‐type interlayers, such as polypyrrole (PPy), polyaniline (PANI), and poly(3,4‐ethylenedioxythiophene) (PEDOT), not only can generate N−S, O−S, S−S, and hydrogen bonds with lithium polysulfides but also can tightly adhere to the polymer separator surface. Nevertheless, these novel conductive polymers are not appropriate for large‐scale production owing to the necessity of precisely controlled polymerization and an unreacted monomer separation process.…”
Section: Introductionmentioning
confidence: 99%
“…PANI, which is electronically conductive, can interact with S species through the imine group. A hybrid coating of PANI and MWCNT was applied onto a PP separator to improve the battery performance of separator (Figure C) . Such a hybrid coating can trap polysulfide species through both chemical bonding and physical absorption.…”
Section: Advanced Separators For Li–s Batteriesmentioning
confidence: 99%
“…Our group has fabricated ion‐selective separators with a Nafion coating layer of 0.7–3.5 mg cm −2 (1.4–7.0 μm) to reject the diffusion of polysulfides . Together with other interlayers of reduced graphene oxide (GO), cellular graphene framework, graphene/TiO 2 , CNTs/PANiNF, as well as functional layers of Al 2 O 3 , glass fiber, GO, SuperP carbon black, carbon nanotube@polyethylene glycol, and poly(acrylic acid), the introduction of binary separators (polymer matrix and functional layer) renders the effective strategy to improve the stable utilization of sulfur.…”
Section: Introductionmentioning
confidence: 99%